Cell-Type Dependence of Stability Modulation of Lectin-initiated Contacts by Impairment of Multivalent Carbohydrate Binding and Intracellular Signaling. Issue 3 (June 2000) - Timoshenko, A. V.; Gorudko, I. V.; André, S.; Gabius, H.-J.
Abstract : Initial ligand selection and the intermolecular spatial arrangement ofglycan-lectin complexes are assumed to be essential to induce formationof stable cell aggregates by a lectin. To distinguish effects of thesetwo processes, the tetrameric mistletoe lectin and its isolated B-chainwere used. A reduced impact of multivalency for Ehrlich ascites tumorcells in contrast to rat thymocytes was revealed. Signaling is thusinitiated in a cell-type-dependent manner. Using selective metabolicinhibitors to reduce signal transfer for aggregate stability, decreasein cellular SH-group level was shown to be a common effect accompanyingsuppression of lectin-dependent aggregate stability. The resultsunderscore an intrinsic variability in the relative importance oflectin-dependent glycan aggregation on the cell surface for triggeringpost-binding lectin effects.